Highly Selective Aerobic Oxidation of 5‐Hydroxymethyl Furfural into 2, 5‐Diformylfuran over Mn–Co Binary Oxides. Issue 23 (16th August 2017) - Gui, Zhenyou; Saravanamurugan, Shunmugavel; Cao, Wenrong; Schill, Leonhard; Chen, Lifang; Qi, Zhiwen; Riisager, Anders
Abstract: A series of Mn−Co binary oxides were prepared by a simple thermal decomposition procedure and evaluated for the aerobic oxidation of 5‐hydroxymethylfurfural (HMF) into 2, 5‐diformylfuran (DFF). Investigation of the effects of metal amounts and calcination temperatures of the prepared catalysts revealed that the Mn−Co binary oxide with a Mn/Co molar ratio of 1/1 showed the best catalytic performance yielding 42.6 % HMF conversion along with 98 % selectivity to DFF after 2 h of reaction. The as‐prepared catalysts were characterized by nitrogen physisorption, X‐ray powder diffraction (XRD), hydrogen temperature‐programmed reduction (H2 ‐TPR) and X‐ray photoelectron spectroscopy (XPS). These results indicated that the Mn−Co binary oxides could increase the Mn 4+ /Mn 3+ atomic ratio and the exposed lattice oxygen content on the surface, thus accelerating the HMF oxidation into DFF. Furthermore, the Mn−Co binary oxides proved to be reusable in five consecutive reaction runs without significant loss of activity. Abstract : Mn−Co binary oxides exhibited high activity and selectivity for aerobic oxidation of 5‐hydroxymethylfurfural (HMF) to 2, 5‐diformylfuran (DFF). The high Mn 4+ /Mn 3+ atomic ratio and the exposed lattice oxygen content on the surface of Mn−Co binary oxides played crucial roles for the enhanced specific activity. Moreover, Mn0.50 ‐Co0.50 ‐O catalyst was prone to recycling for at least five times without significant loss of its activity